Analysis of Historical Values and Family Dynamics Amidst the 1998 Riots in The Movie “Di Balik 98” (Universitas Pendidikan Indonesia, 2024)
The 1998 riots were one of Indonesia's darkest events at the end of the New Order era, the reign of President Soerharto. These riots were caused by the multidimensional crisis around 1997-1998 which culminated in the May 1998 tragedy. The movie